Education in Information Science Some Basic Issues - Raghavan, K.S. (DESIDOC Journal of Library & Information Technology, 2002)
This paper addresses the implications of technological changes occurring in information sector on the education and training of information professionals. The author presents objectives, contents, organisation of information, manpower development and other issues in current perspective. The paper stresses an information technology oriented approach towards customer and the need for satisfying the end user. The information professional has to be constantly in touch with technological changes and be able to design, develop, and implement different types of databases. The author has proposed a mode! structure of curricula and courses for information sector. http://dx.doi.org/10.14429/dbit.15.6.3209